ESTIMATION PILOTING ERRORS STATISTICS AND PROBABILITY OF SATELLITE NAVIGATION SYSTEM FAILURE - V. L. Kuznetsov; E. S. Goryachenkova (Научный вестник МГТУ ГА, 2016)
A new approach to the problem of co-processing of data about the aircraft position with the help of satellite navigation systems and secondary surveillance radar system is been developed. The purpose of the task is to obtain estimates of mistakes distribution for control systems and piloting errors. Possibility of a statistical relationship between piloting errors and mistakes of satellite navigation system is taken into account.